2009
DOI: 10.1371/journal.pone.0005981
|View full text |Cite
|
Sign up to set email alerts
|

Increased Frequency and Compromised Function of T Regulatory Cells in Systemic Sclerosis (SSc) Is Related to a Diminished CD69 and TGFβ Expression

Abstract: BackgroundRegulatory T cells (Tregs) are essential in the control of tolerance. Evidence implicates Tregs in human autoimmune conditions. Here we investigated their role in systemic sclerosis (SSc).Methods/Principal FindingsPatients were subdivided as having limited cutaneous SSc (lcSSc, n = 20) or diffuse cutaneous SSc (dcSSc, n = 48). Further subdivision was made between early dcSSc (n = 24) and late dcSSc (n = 24) based upon the duration of disease. 26 controls were studied for comparison. CD3+ cells were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
103
4
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(115 citation statements)
references
References 62 publications
5
103
4
3
Order By: Relevance
“…This fact could explain the presence of high values of Tregs in neonates and the negative correlation between Treg frequency and GA. In fact, we observed that absolute counts and percentage of Tregs in both preterm and full-term infants are higher than the values reported in the literature for children (17) and adults (35). The presence of increased values of Tregs in preterm infants would play a protective role in maternal-fetal tolerance but could have a secondary effect by which Tregs inhibit the survival and proliferation of lymphocytes and other immune cells.…”
Section: Leukopenia In Preterm Infants and Tregscontrasting
confidence: 64%
“…This fact could explain the presence of high values of Tregs in neonates and the negative correlation between Treg frequency and GA. In fact, we observed that absolute counts and percentage of Tregs in both preterm and full-term infants are higher than the values reported in the literature for children (17) and adults (35). The presence of increased values of Tregs in preterm infants would play a protective role in maternal-fetal tolerance but could have a secondary effect by which Tregs inhibit the survival and proliferation of lymphocytes and other immune cells.…”
Section: Leukopenia In Preterm Infants and Tregscontrasting
confidence: 64%
“…In SSc patients, few studies investigated the various Treg subsets and their suppressive function, these also with conflicting results, showing either reduced, 20-22 increased 23,24 or the same [25][26][27] number of circulating Treg cells in peripheral blood as compared with controls. These discrepancies might be mostly due to variations in study techniques, with setting analysis of either CD4 þ CD25 þ , 21,23 CD4 þ CD25 high , 12,25,26 20,24,26 CD25 þ Foxp3 þ CD127 -23 or CD4 þ CD25 high CD127 low subsets. 22 Despite these controversies, in most of these studies of SSc patients' samples, 22,23,26 impaired Treg-suppressive function was associated with SSc disease severity.…”
Section: Introductionmentioning
confidence: 99%
“…These discrepancies might be mostly due to variations in study techniques, with setting analysis of either CD4 þ CD25 þ , 21,23 CD4 þ CD25 high , 12,25,26 20,24,26 CD25 þ Foxp3 þ CD127 -23 or CD4 þ CD25 high CD127 low subsets. 22 Despite these controversies, in most of these studies of SSc patients' samples, 22,23,26 impaired Treg-suppressive function was associated with SSc disease severity. Of interest, Klein 1 et al 26 reported that there was a reduction in Treg within the skin, but not in the peripheral blood of SSc patients.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Although the aetiology of SSc is not yet understood, there are evidences strongly suggesting that misregulation of T regs may underlie the immune dysfunction in the progression of this disease. 20,21 Interestingly, it has been proposed that skin-specific T reg anomalies could be crucial in the SSc pathogenesis. 21 As IL2RA has an important role in T reg regulation, 2 genetic alteration of its encoding gene could have serious consequences in the function of this cell type by altering the IL2/IL2R signalling.…”
Section: Discussionmentioning
confidence: 99%